Identification of Rhizospheric Bacterial Diversity in Mangrove Ecosystems in Tanah Laut Regency - Nisrina Ramadhani; Guruh Mayka Putra; Akhmad Rizali (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Mangrove ecosystem is rich in rhizosphere bacteria that support the nutrient cycle and environmental balance. This study aims to identify the diversity of rhizosphere bacteria from mangrove soils in Tanah Laut Regency, South Kalimantan. Samples were taken from three types of mangrove density tight, medium, and rare, at depths of 0-30 cm and 30-60 cm. Tiered dilution to level 10-8, dilution level 10-5 to 10-8 are inoculated on NA media and purified. The purification results obtained a total of 29 isolats, in the dense mangrove type there were 14 isolats, medium mangroves 8 isolats, and rare mangroves 7 isolats. Morphological analysis showed macroscopic variation with round, entire, undulate, and irregular colony margins. There are white, yellow, beige, and orange colors. Elevation consists of flat, raised, to convex. The size of the colony is small to moderate. Microscopic analysis based on the results of gram staining there are groups with positive and negatif grams, in the form of coccus cells, bacillus, and coccobacillus. Growth assays on pH 3, 5, 7, and 9 indicated optimal growth at pH 7, with strong inhibition at pH 3. These results confirm that there is a high level of diversity of mangrove rhizosphere bacteria.